2010
DOI: 10.1136/thx.2009.123083
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pulmonary complications following thoracic surgery: are there any modifiable risk factors?

Abstract: Background Postoperative pulmonary complications (PPC) are the most frequently observed complications following lung resection, of which pneumonia and atelectasis are the most common. PPCs have a significant clinical and economic impact associated with increased observed number of deaths, morbidity, length of stay and associated cost. The aim of this study was to assess the incidence and impact of PPCs and to identify potentially modifiable independent risk factors. Methods A prospective observational study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
305
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(335 citation statements)
references
References 29 publications
16
305
2
12
Order By: Relevance
“…[1][2][3] This is a major concern as up to 20% of surgical patients are smokers. 4,5 A recent large observational study of non-cardiac surgical patients reported that smoking is associated with a 38% increase in the risk of perioperative death and a 30-109% increase in the risk of serious postoperative complications, depending on the type of complication. 3 However, this study did not examine whether short-term abstinence from smoking before surgery reduces the risk of postoperative complications.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] This is a major concern as up to 20% of surgical patients are smokers. 4,5 A recent large observational study of non-cardiac surgical patients reported that smoking is associated with a 38% increase in the risk of perioperative death and a 30-109% increase in the risk of serious postoperative complications, depending on the type of complication. 3 However, this study did not examine whether short-term abstinence from smoking before surgery reduces the risk of postoperative complications.…”
Section: Résumémentioning
confidence: 99%
“…4,5 A recent large observational study of non-cardiac surgical patients reported that smoking is associated with a 38% increase in the risk of…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, the patients undergoing lung cancer surgery are susceptible to pulmonary complications because of pain, secretory retention, inefficient cough, and decreased immunity. Postoperative pneumonia (POP) is one of the most frequent complications following thoracic surgery and is strongly associated with high mortality rates (2,3). Many perioperative risk factors have been reported to be associated with an increased incidence of pneumonia after surgery (2,(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence rate of postoperative pulmonary complications (PCs) ranging from 15% to 37% for patients who undergo lobectomy (4)(5)(6), in which prolonged air leak and pneumonia are the most common (7)(8)(9). PCs prolong hospitalization, ICU care, increased medical cost (9,10), but limited researches focus on the potential impact of PCs on long-term survival for lung cancer patients (11).…”
Section: Introductionmentioning
confidence: 99%